2015
DOI: 10.1128/jvi.02361-14
|View full text |Cite
|
Sign up to set email alerts
|

Superinfection with Woodchuck Hepatitis Virus Strain WHVNY of Livers Chronically Infected with Strain WHV7

Abstract: The determinants of the maintenance of chronic hepadnaviral infection are yet to be fully understood. A long-standing unresolved argument in the hepatitis B virus (HBV) research field suggests that during chronic hepadnaviral infection, cell-to-cell spread of hepadnavirus is at least very inefficient (if it occurs at all), virus superinfection is an unlikely event, and chronic hepadnavirus infection can be maintained exclusively via division of infected hepatocytes in the absence of virus spread. Superinfectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…In a separate study, we compared strains WHV7 and WHVNY and concluded that the two strains were quite similar in terms of their replication parameters and the ability to induce productive acute infection in naive adult woodchucks (16). This result was consistent with the interpretation that the observed limited efficiency of WHVNY superinfection in vivo (15) was not mediated by the properties of WHVNY virions but rather reflected the properties of hepatocytes residing in livers chronically infected with WHV7. In another study, we compared the infectivity of different types of HDV virions that differed only by the nature of the envelope proteins which coated the virions.…”
supporting
confidence: 77%
See 4 more Smart Citations
“…In a separate study, we compared strains WHV7 and WHVNY and concluded that the two strains were quite similar in terms of their replication parameters and the ability to induce productive acute infection in naive adult woodchucks (16). This result was consistent with the interpretation that the observed limited efficiency of WHVNY superinfection in vivo (15) was not mediated by the properties of WHVNY virions but rather reflected the properties of hepatocytes residing in livers chronically infected with WHV7. In another study, we compared the infectivity of different types of HDV virions that differed only by the nature of the envelope proteins which coated the virions.…”
supporting
confidence: 77%
“…After the resuspension, 40 l of each DNA sample was incubated at 37°C overnight in a 500-l reaction mixture, which contained 1ϫ NEB (New England BioLabs) buffer 4, 1 mM ATP, 40 g/ml of RNase A, and 50 U of plasmid-safe ATP-dependent DNase (Epicentre). Upon completion of the incubation, cccDNA was further isolated by extraction with phenol and a second extraction with a phenolchloroform mixture followed by ethanol precipitation (15). The measurements of cccDNA amounts were conducted using qPCR.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations